Simultaneous over-expression of PaSOD and RaAPX in transgenic Arabidopsis thaliana confers cold stress tolerance through increase in vascular lignifications. - Amrina Shafi (Public Library of Science (PLoS), 2014)
Antioxidant enzymes play a significant role in eliminating toxic levels of reactive oxygen species (ROS), generated during stress from living cells. In the present study, two different antioxidant enzymes namely copper-zinc superoxide dismutase derived from Potentilla astrisanguinea (PaSOD) and ascorbate peroxidase (RaAPX) from Rheum austral both of which are high altitude cold niche area plants of Himalaya were cloned and simultaneously over-expressed in Arabidopsis thaliana to alleviate cold stress. It was found that the transgenic plants over-expressing both the genes were more tolerant to cold stress than either of the single gene expressing transgenic plants during growth and development. In both single (PaSOD, RaAPX) and double (PaSOD + RaAPX) transgenic plants higher levels of total antioxidant enzyme activities, chlorophyll content, total soluble sugars, proline content and lower levels of ROS, ion leakage were recorded when compared to the WT during cold stress (4°C), besides increase in yield. In the present study, Confocal and SEM analysis in conjunction with qPCR data on the expression pattern of lignin biosynthetic pathway genes revealed that the cold stress tolerance of the transgenic plants might be because of the peroxide induced up-regulation of lignin by antioxidant genes mediated triggering.